Considerations for career intervention services in global youth workforce development: consensus across policy, research, and practice - Sylvia Nassar; Aisha Al-Qimlass; Nurten Karacan-Ozdemir; Lynn Z. Tovar (Empirical Research in Vocational Education and Training, 2019)
Abstract As yet, despite ongoing gaps in educational and career achievement, earning potential, and other psychosocial risks that perpetuate marginalization among certain populations globally, elements of effective career education and interventions have yet to be agreed upon. Thus, we sought consensus among experts across the domains of policy, research, and practice. We detail the process and results of a recent Delphi study conducted with global youth career and workforce development experts across policy, research, and practice domains who were surveyed about their opinions regarding concepts such as ecological perspectives, needs assessment, trainer preparation, participant curriculum, curriculum delivery, and program evaluation—the six emergent areas of a recent comprehensive synthesis of the literature across these domains (Nassar and Al-Qimlass, in Career builders: key components for effective global youth career and workforce development. RTI Press, Research Triangle Park, 2017a). Our Delphi study yielded 199 consensus statements, subsequently organized into 28 themes, or considerations, for effective global workforce development initiatives. In conclusion, we provide implications, including implementation strategies for key stakeholder groups.